Dentists' attitudes towards acute pharmacological pain management in children and adolescents. Issue 2 (10th July 2017) - Berlin, Henrik; List, Thomas; Ridell, Karin; Klingberg, Gunilla
Abstract : Aim: This study aimed to investigate Swedish dentists' attitudes regarding pain management strategies for treating children and adolescents. It assessed recommendations for pre‐ and postoperative analgesics, and use of local anaesthesia, and whether application of these strategies differs between general dental practitioners (GDPs) and specialists in paediatric dentistry (SPDs). Design: We invited all GDPs ( n = 807) in southern Sweden (Region Skåne), and all registered SPDs ( n = 122) working in Sweden (929 actively practising dentists under age 65 years) to participate in a postal survey on pain management in paediatric dental care. Results: The SPDs reported using all types of pain‐reducing strategies more frequently than GDPs except local anaesthesia when extracting a permanent premolar, which SPDs and GDPs used equally often. Preoperative analgesic use was greater among SPDs than GDPs. GDPs used local anaesthesia less frequently for filling therapy in primary teeth than in permanent teeth. Conclusions: SPDs recommend preoperative analgesics more often than GDPs do. GDPs seem to underuse local anaesthetics when treating children and adolescents. SPDs also use pain management strategies more frequently than GDPs. Among GDPs, pain management is less frequent when treating primary teeth than permanent teeth.